Joint replacement for avascular necrosis in people living with HIV - Pisanu, Francesco; Fiore, Vito; Corradi, Martina; Esposito, Elisabetta; Maida, Ivana; Caggiari, Gianfilippo; Ciatti, Corrado; Manunta, Andrea Fabio; Doria, Carlo (Acta Biomedica Atenei Parmensis, 2022)
Recently, the interest on multifocal avascular necrosis (AVN) among people living with HIV (PLWH) is rising. PLWH have an incidence of symptomatic AVN significantly higher than the general population. The chronic viral infection may induce a direct damage via necrotizing vasculitis, on the other hand the highly active antiretroviral therapy represents a probable risk factor as it can indirectly lead to multifocal necrosis. Regardless of etiopathology, the AVN management in PLWH is the same as in the general population. Depending on symptoms, stage, and location, the AVN can be treated conservatively or surgically, but in its final stages joint replacement is often the most appropriate therapeutic option. The safety and outcomes of such major orthopedic surgery in PLWH are debated topics. In agreement with the literature in our case series we observed, despite some complication, a significant pain relief and excellent recovery of function after hip replacements. Although increased complication rates, several other independent risk factors associated with HIV infection can act as confounding factors. These confounders must be taken into account both in clinical practice and in data analysis. This case-based review highlights the increasing incidence of AVN in PLWH, and emphasizes the safety and effectiveness of the prosthetic joint replacement in this population.